Path Chromatic Index of the Composition of Sone Special Graphs - Undang, Sushela Marie; Lemence, Richard; Buenavista, Rolando; Benitez, Julius (ASIA PACIFIC JOURNAL OF SOCIAL INNOVATION, 2024)
Path chromatic index is one of the many coloring invariants of graphs. H.C. Serate [6] had presented an in-depth study of such coloring invariant. However, no_ne has been established in the path chromatic index of the composition of graphs. Hence, the goal of this paper is to determine the path chromatic index of some special graphs.